Roman Britain and the English settlements - Collingwood, R. G. (Robin George), 1889-1943; Myres, John Linton, Sir, 1869-1954 (Oxford, The Clarendon press, 1936)
2nd ed. repr. 1945.
Bibliography: p. [462]-489.
Keywords: Romans -- Great Britain; Great Britain -- History -- Roman period, 55 B.C.-449 A.D.; Great Britain -- History -- Anglo-Saxon period, 449-1066.